2017
DOI: 10.1371/journal.pone.0188885
|View full text |Cite
|
Sign up to set email alerts
|

Application of non-invasive low strength pulsed electric field to EGCG treatment synergistically enhanced the inhibition effect on PANC-1 cells

Abstract: Traditional therapies for pancreatic cancer are usually expensive and likely to cause side effects, and most patients have the risk of recurrence and suffering pain. Here, we investigated combination treatment of epigallocatechin-3-gallate (EGCG) and non-invasive low strength pulsed electric field (PEF) on the human pancreatic cell line PANC-1. Cells were cultured in various concentrations of EGCG and exposed to trains of PEF. The results showed that the low strength PEF alone or single treatment with low conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…These effects basically arise from its abilities to promote pro-apoptotic effects, inhibit angiogenesis, regulate cellular metabolic pathways, and reduce inflammatory factors [28,35]. EGCG can increase the activities of traditional anticancer treatments [36][37][38] and reverse drug cell resistance, and this has encouraged its use in clinical trials for treatments of various types of cancer and other diseases [39]. Acacia catechu Willd.…”
Section: Discussionmentioning
confidence: 99%
“…These effects basically arise from its abilities to promote pro-apoptotic effects, inhibit angiogenesis, regulate cellular metabolic pathways, and reduce inflammatory factors [28,35]. EGCG can increase the activities of traditional anticancer treatments [36][37][38] and reverse drug cell resistance, and this has encouraged its use in clinical trials for treatments of various types of cancer and other diseases [39]. Acacia catechu Willd.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that exposure to non-invasive, low-intensity PEF (LIPEF) has strengthened the effect of low-dose curcumin in combating human pancreatic cancer PANC-1 cells [16]. Our team also observed the consistent effect of non-invasive LIPEF in significantly enhancing EGCG activity in human pancreatic cancer cells [17]. It is noteworthy that LIPEF alone did not harm the cells, underscoring its safety and non-toxicity.…”
Section: Introductionmentioning
confidence: 60%
“…As a viable method in the application of physical stimuli, non-invasive PEF features external application of electric pulse to the desired area. In practice, the use of non-invasive PEF to enhance the activity of anticancer agent and lower the required dosage of agent is significantly effective, as proven by our recent studies on polyphenols with this approach [16,17]. It was found that exposure to non-invasive, low-intensity PEF (LIPEF) has strengthened the effect of low-dose curcumin in combating human pancreatic cancer PANC-1 cells [16].…”
Section: Introductionmentioning
confidence: 99%
“…The device for exposure of the cells to the PEF was performed as we previously described [ 4 ]. Following the US stimulation, the cells were placed between two copper flat and parallel electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have reported that a non-invasive low strength pulsed electric field (PEF) can enhance the epigallocatechin gallate (EGCG) to combat against the pancreatic cancer cells [ 4 ]. It was found that the synergistic reactions in the double treatment of the EGCG and PEF disturbed the mitochondria, enhanced the intrinsic pathway transduction, and effectively induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%